PEWARISAN SIFAT WARNA DAN TIPE BIJI JAGUNG MANADO KUNING - Pamandungan, Yefta; Ogie, Tommy B. (EUGENIA, 2018)
ABSTRACT This research aims to study 1) Maternal effect on the inheritance of yield components of Manado Yellow Corn, and 2) Inheritance of seed colour and seed type of Manado Yellow Corn. Research conducted in Kalasey village, Mandolang subdistrict, Minahasa regency, Province of North Sulawesi from April to September 2016. The plant material used is a local variety of Manado Yellow Corn that collectedin the laboratory of Plant Science, Faculty of Agriculture, University of Sam Ratulangi, Manado. This research was arranged to compare two hybridization treatments, from two parent population, that is: 1) Local corn with yellow seed colour and flint seed type, 2) Local corn with yellow seed colour and dent seed type. Each treatment consisted of four replicates and each of replicating consisted of six female plants so that there were 24 ears from parents hybridization and (F1) and 24 ears of reciprocal hybridization (F1R). The results showed that 1) There was not maternal effect on the inheritance of yield components, such as the weight of the ear, length of the ear, the diameter of the ear, number of seed row per ear, number of yellow seed color and number of dent seed type with crossed the parent of Manado Yellow corn, 2) There was maternal effect on inheritance of flint seed type with crossed the parent of Manado Yellow corn and 3) The highest percentage of yellow seed color and flint seed type, the character of Manado Yellow Corn, obtained from crossing parents ♀ Flint × ♂ Dent.Keywords: dent, flint, anado yellow corn